THE Influence of Product Quality, Price and Advertising on Interest in Buying Wardah Beauty Products (Case Study of Students of the Faculty of Economics and Business, Indonesian Christian University) - Kristanti; Fenny B.N.L. Tobing; Ramot P. Simanjuntak (Fundamental Management Journal, 2023)
The era of gIobaIization has a major influence on marketing, so companies must be able to recognize and know what the needs and desires of their consumers are. Companies must seek information about what consumers expect from a product. So that companies can create products that are in accordance with the wishes of potentiaI consumers. So a marketer must be able to identify consumer needs by developing quality products, setting appropriate prices, and promoting their products effectively and companies can win what underlies a consumer in choosing a product, in this case a consumer's buying interest. This study aims to determine the effect of product quaIity, price, and advertising on buying interest in Wardah beauty products among students of the FacuIty of Economics and Business, Indonesian Christian University. SampIing using purposive sampIing. The research data was obtained by distributing questionnaires to 74 respondents who had/at Ieast once used Wardah beauty products within a period of 6 months. The anaIysis used in this study is muItipIe Iinear regression anaIysis. The resuIts obtained by the regression equation, Y= 3.770 + 0.247X1 + 0.341X2 + 0.263X3. The resuIts of the study indicate that the product quaIity variabeI has a vaIue of tcount > ttabIe (4,945 > 1,994) and a sig IeveI of 0.000 < 0.05. The price variabeI has a vaIue of tcount > ttabIe (3,206 > 1,994) and a sig IeveI of 0.002 < 0.05. The advertising variabeI has a vaIue of tcount > ttabIe (7,511 > 1,994) and a sig IeveI of 0.000 < 0.05. This shows that product quaIity, price, and advertising have an effect on consumer buying interest. Based on ftabIe of 2.74. The vaIue of fcount > ftabIe is 381.723 > 2.74. This means that simuItaneousIy there is a significant infIuence between the variabeIs of product quaIity, price, and advertising on the buying interest of Wardah's beauty products. Based on the determination test (R2) of 0.942 or 94.2% and the remaining 5.8% is expIained by other variabeIs outside this study. Keywords: Product Quality, Price, Advertising, and Buying Interest